Age Is a Determining Factor of Dry Eye-Related Signs and Symptoms - Masahiko Ayaki; Kazuno Negishi; Motoko Kawashima; Miki Uchino; Minako Kaido; Kazuo Tsubota (Diagnostics, 2020)
Purpose: The reported signs and symptoms of dry eye (DE) have been discordant. This study evaluated risk factors of DE-related symptoms and signs to explore their association with patient demographics, focusing on the age factor. Methods: The study enrolled 704 consecutive patients visiting general eye clinics who complained of ocular discomfort, but had normal vision. The patients were asked about the presence of six common symptoms related to DE and, tear break-up time (TBUT). The severity of patients’ keratopathy was also examined, and patients underwent Schirmer’s test. Results: Logistic regression analysis demonstrated that younger age (≤29 years) was associated with non-visual symptoms and keratopathy, while older age (≥60 years) was associated with short TBUT and low values on Schirmer’s test. Middle age was associated with both severe symptoms and signs. Conclusions: Discrepancies in the signs and symptoms of DE may depend, in part, on age, with younger subjects showing severe non-visual symptoms with apparently normal tear function and severe keratopathy, and older subjects showing fewer symptoms and less severe keratopathy despite worse tear function.